2020
DOI: 10.3390/jcm9082506
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Kidney: From Epidemiology to Clinical Practice

Abstract: The new respiratory infectious disease coronavirus disease 2019 (COVID-19) that originated in Wuhan, China, in December 2019 and caused by a new strain of zoonotic coronavirus, named severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), to date has killed over 630,000 people and infected over 15,000,000 worldwide. Most of the deceased patients had pre-existing comorbidities; over 20% had chronic kidney disease (CKD). Furthermore, although SARS-CoV-2 infection is characterized mainly by diffuse alveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 159 publications
(296 reference statements)
3
101
1
10
Order By: Relevance
“…AKI in COVID-19 patients is most likely due to multiple mechanisms [ 60 ]. The first is invasion of the virus in the kidney, in which high ACE2 expression may play a role [ 61 ].…”
Section: Covid-19 and Akimentioning
confidence: 99%
“…AKI in COVID-19 patients is most likely due to multiple mechanisms [ 60 ]. The first is invasion of the virus in the kidney, in which high ACE2 expression may play a role [ 61 ].…”
Section: Covid-19 and Akimentioning
confidence: 99%
“…In a recent study based on the analysis of several clinical reports, Gagliardi et al [85] related that up to 15% of the hospitalized COVID-19 patients had at least one kidney abnormality represented by increased BUN and reduced GFR, as well as 26-63% of patients presented proteinuria at admission or developed proteinuria during their stay in hospital. Moreover, the incidence of AKI in COVID-19 patients varied from 0.5% to 23%, with an interval from baseline visit to the onset of AKI of 7-15 days in median, and that mortality from the COVID-19 patients who developed AKI could be up to 13 times higher than those infected patients without clinical signs of AKI.…”
Section: Coronavirus and Acute Kidney Injurymentioning
confidence: 99%
“…Moreover, the incidence of AKI in COVID-19 patients varied from 0.5% to 23%, with an interval from baseline visit to the onset of AKI of 7-15 days in median, and that mortality from the COVID-19 patients who developed AKI could be up to 13 times higher than those infected patients without clinical signs of AKI. In addition, the authors suggested that the high prevalence of kidney involvement at hospital admission of some COVID-19 patients may be associated with some factors, including report of previous renal impairments, patients' age, severity of illness, and presence of diabetes and/or heart failure, which are all risk factors for AKI that contribute to a pro-inflammatory state with functional defects in their immune system, worsening the clinical conditions of COVID-19 patients [85].…”
Section: Coronavirus and Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Current data [7] revealed that the impact of COVID-19 presents certain peculiar aspects in different nations that have been deeply investigated. Some authors hypothesised that virus mutations were responsible for these differences [8,9,10]. Nevertheless, many independent studies agreed that the mutations did not have a primary role in the differentiation of the outcomes [11,12,13].…”
Section: Introductionmentioning
confidence: 99%